1987
DOI: 10.1042/bj2460279
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic conversion of proinsulin into insulin. Identification of a Ca2+-dependent acidic endopeptidase in isolated insulin-secretory granules

Abstract: The nature of the endoproteolytic activity involved in the post-translational processing of proinsulin has been investigated in rat insulinoma tissue. 125I-proinsulin was converted by lysed insulin-secretory granules into insulin via an intermediate form identified as des-dibasic-proinsulin. This activity co-localized with immunoreactive (endogenous) insulin and carboxypeptidase H upon subcellular fractionation of the tissue, indicating a secretory-granular location. Under optimized conditions, conversion was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…It is possible that similar proteases are involved in the processing of other mammalian proproteins. Very recently, Davidson et al [20] identified a similar enzyme in insulin-secretory granules. This Ca2÷-dependent protease, which correctly processes proinsulin, is quite distinct from any previously proposed proinsulin convertase, but is remarkably similar to the proalbumin convertase described here in terms of its subcellular location, inhibitory properties and pH optimum (pH 5.0-6.0).…”
Section: Resultsmentioning
confidence: 97%
“…It is possible that similar proteases are involved in the processing of other mammalian proproteins. Very recently, Davidson et al [20] identified a similar enzyme in insulin-secretory granules. This Ca2÷-dependent protease, which correctly processes proinsulin, is quite distinct from any previously proposed proinsulin convertase, but is remarkably similar to the proalbumin convertase described here in terms of its subcellular location, inhibitory properties and pH optimum (pH 5.0-6.0).…”
Section: Resultsmentioning
confidence: 97%
“…Various enzymes, including serine proteases, have been localized to insulin-producing cells (14,15,(35)(36)(37)(38)(39), which basically may cleave CGA into smaller fragments. Moreover, single basic residues in proline-containing regions of proteins (as in the C terminus of CST within the CGA sequence) define a preferential or specific cleavage site in various precursors of regulatory peptides including pancreatic icosapeptide, gastrin-releasing peptide, or atrial natriuretic polypeptide (26).…”
Section: Resultsmentioning
confidence: 99%
“…There are important sequence differences at both the B-chain/ C-peptide and C-peptide/A-chain cleavage sites between the human and rodent proinsulins (Sizonenko & Halban 1991). The processing of human proinsulin occurs at sites marked by the sequence Lys-Thr-Arg-Arg and Leu-GlnLys-Arg, which are cleaved by the endoproteases PC1 and PC2 respectively (Davidson et al 1987). These enzymes work sequentially and thus little cleavage of the C-peptide/A-chain junction by PC2 occurs in the absence of prior cleavage at the B-chain/C-peptide junction by PC1 (Jackson et al 1997).…”
Section: Discussionmentioning
confidence: 99%